Connect with a global community of knowledgeable individuals on IDNLearn.com. Get comprehensive answers to all your questions from our network of experienced experts.
Sagot :
Let's find each of the values step-by-step.
### Finding [tex]\( f(7) \)[/tex]:
Given the function:
[tex]\[ f(x) = -4 + \sqrt{-2 + x} \][/tex]
Substitute [tex]\( x = 7 \)[/tex]:
[tex]\[ f(7) = -4 + \sqrt{-2 + 7} \][/tex]
[tex]\[ f(7) = -4 + \sqrt{5} \][/tex]
So,
[tex]\[ f(7) \approx -1.7639320225002102 \][/tex]
### Finding [tex]\( g(-3) \)[/tex]:
Given the function:
[tex]\[ g(x) = 2 \left| -4 + x \right| \][/tex]
Substitute [tex]\( x = -3 \)[/tex]:
[tex]\[ g(-3) = 2 \left| -4 + (-3) \right| \][/tex]
[tex]\[ g(-3) = 2 \left| -7 \right| \][/tex]
[tex]\[ g(-3) = 2 \cdot 7 \][/tex]
[tex]\[ g(-3) = 14 \][/tex]
So,
[tex]\[ g(-3) = 14 \][/tex]
### Finding [tex]\( h(-2) \)[/tex]:
Given the function:
[tex]\[ h(x) = \frac{-4 x^2 + 6}{x^2} \][/tex]
Substitute [tex]\( x = -2 \)[/tex]:
[tex]\[ h(-2) = \frac{-4 (-2)^2 + 6}{(-2)^2} \][/tex]
[tex]\[ h(-2) = \frac{-4 \cdot 4 + 6}{4} \][/tex]
[tex]\[ h(-2) = \frac{-16 + 6}{4} \][/tex]
[tex]\[ h(-2) = \frac{-10}{4} \][/tex]
[tex]\[ h(-2) = -2.5 \][/tex]
So,
[tex]\[ h(-2) = -2.5 \][/tex]
Combining all the results:
[tex]\[ \begin{array}{c} f(7) \approx -1.7639320225002102 \\ g(-3) = 14 \\ h(-2) = -2.5 \\ \end{array} \][/tex]
### Finding [tex]\( f(7) \)[/tex]:
Given the function:
[tex]\[ f(x) = -4 + \sqrt{-2 + x} \][/tex]
Substitute [tex]\( x = 7 \)[/tex]:
[tex]\[ f(7) = -4 + \sqrt{-2 + 7} \][/tex]
[tex]\[ f(7) = -4 + \sqrt{5} \][/tex]
So,
[tex]\[ f(7) \approx -1.7639320225002102 \][/tex]
### Finding [tex]\( g(-3) \)[/tex]:
Given the function:
[tex]\[ g(x) = 2 \left| -4 + x \right| \][/tex]
Substitute [tex]\( x = -3 \)[/tex]:
[tex]\[ g(-3) = 2 \left| -4 + (-3) \right| \][/tex]
[tex]\[ g(-3) = 2 \left| -7 \right| \][/tex]
[tex]\[ g(-3) = 2 \cdot 7 \][/tex]
[tex]\[ g(-3) = 14 \][/tex]
So,
[tex]\[ g(-3) = 14 \][/tex]
### Finding [tex]\( h(-2) \)[/tex]:
Given the function:
[tex]\[ h(x) = \frac{-4 x^2 + 6}{x^2} \][/tex]
Substitute [tex]\( x = -2 \)[/tex]:
[tex]\[ h(-2) = \frac{-4 (-2)^2 + 6}{(-2)^2} \][/tex]
[tex]\[ h(-2) = \frac{-4 \cdot 4 + 6}{4} \][/tex]
[tex]\[ h(-2) = \frac{-16 + 6}{4} \][/tex]
[tex]\[ h(-2) = \frac{-10}{4} \][/tex]
[tex]\[ h(-2) = -2.5 \][/tex]
So,
[tex]\[ h(-2) = -2.5 \][/tex]
Combining all the results:
[tex]\[ \begin{array}{c} f(7) \approx -1.7639320225002102 \\ g(-3) = 14 \\ h(-2) = -2.5 \\ \end{array} \][/tex]
Your participation means a lot to us. Keep sharing information and solutions. This community grows thanks to the amazing contributions from members like you. IDNLearn.com has the solutions you’re looking for. Thanks for visiting, and see you next time for more reliable information.